Networked Gatekeeping and Networked Framing on Twitter Protests in Mexico about the Ayotzinapa Case - Galarza Molina, Rocío Araceli (Hipatia Press, 2019)
This research focuses on a Twitter protest about the disappearance of 43 students in Mexico in 2014 –known as the Ayotzinapa case– which used the hashtag #PaseDeLista1al43. Social network analysis, interviews and thematic analyses of 3,616 tweets were conducted to investigate how networked gatekeeping and networked framing processes occurred within this networked public. Results show that on this digital protest, elite and non-elite Twitter users were in charge of gatekeeping activities, collaborating to maintain the discussion of the topic of the missing students. The analysis of frames revealed that the protest sought to: humanize the case emphasizing the life of the students; assign responsibility; and portray itself as a way to take an active role and coping emotionally with the disappearance. This works contributes to the literature on networked publics, combining network analysis with interviews to look beyond the digital footprint of the protest to listen to the perspectives of protesters, providing an insight into the dynamics of gatekeeping and framing within a network. Given the porosity, openness, and permanence of Twitter, results from such collaborative relationship of elite and non-elite voices to protest about an issue are now harder to ignore in the public sphere.